Hubungan Antara Pengetahuan, Sikap, dan Perilaku Karyawan dengan Penerapan Manajemen Budaya Keselamatan dan Kesehatan Kerja - Endang Purnawati Rahayu (STIKes Hang Tuah Pekanbaru, 2015)
Safety culture affected by the organization, individual, and workplace. This research to analyze the relation of knowledge, attitudes and behavior an employee with the application of Occupational Safety and Health (OHS) in Production Department of PT. Mustika Ratu. This research uses a quantitative approach using 34 questions of the questionnaire and the total sample as many as 170 a person taken in simple random sampling. Research result: 85.9 % of respondents had a good knowledge on implementing OHS’s cultural management, 80.6 % have a good attitude and 84.7 % have a good behavior on cultural implementation of OHS. Implementation of safety management of cultural given good results: 89.4 % had implemented OHS’s cultural management. As to the relation between knowledge, attitudes and behavior towards the implementation on OHS’s cultural management, the study of sub variables gave the same result, namely a significant relationship. The relation on knowledge to the OHS's cultural management with p Value < 0.001 and Odd Ratio 9.133 ( 95 % CI = 3.143 to 26.539). The relation on atitude to (PValue < 0.001) and Odd Ratio = 9.286 (95 % CI = 3.250 to 26.531), whilst the relation between behavior to the OHS's cultural management with p Value < 0.001 and Odd Ratio = 5.956 ( 95 % CI = 2.080 to 17.051 ). Another finding in this study was, there were no significant relations between respondent characteristics and the implementation of OHS’s cultural. The recommendation: the management have to conduct monitoring and must have a good communication with the employees, train and engage the employees to improved the company's effort on implementing OHS with the implementation of OSHAS 18001 due to Law number 1 of 1970 and PP (government regulation) number 50 in 2012.